Effect of a novel animal milk oligosaccharide biosimilar on macronutrient digestibility and gastrointestinal tolerance, fecal metabolites, and fecal microbiota of healthy adult cats. (15th December 2020) - Oba, Patrícia M; Lee, Anne H; Vidal, Sara; Wyss, Romain; Miao, Yong; Adesokan, Yemi; Swanson, Kelly S
Abstract: GNU100 is a novel animal milk oligosaccharide (AMO ) biosimilar. In a recent in vitro fermentation study, GNU100 was shown to be fermentable by feline gastrointestinal microbiota and lead to increased short-chain fatty acid production. Our objectives herein were to evaluate the palatability, safety, and gastrointestinal tolerance of GNU100 in healthy adult cats. Exploratory end-points were measured to assess utility. In study 1, 20 adult cats were used to test the palatability of diets containing 0% or 1% GNU100. In study 2, 32 (mean age = 1.9 yr; mean body weight = 4.6 kg) male ( n = 12) and female ( n = 20) adult cats were used in a completely randomized design. After a 2-wk baseline, cats were assigned to one of the following treatment groups and fed for 26 wk: control (CT, no GNU100), low dose (LD, 0.5% GNU100), medium dose (MD, 1.0% GNU100), and high dose (HD, 1.5% GNU100). On weeks 2, 4, and 26, fresh fecal samples were collected for the measurement of stool quality and immune and inflammatory markers and on weeks 2 and 4 for microbiota and metabolites. On week 4, total feces were collected to measure apparent total tract macronutrient digestibility. On weeks 2, 4, and 26, blood samples were collected for serum chemistry, hematology, and inflammatory marker measurement. The palatability test showed that 1% GNU100 was strongly preferred ( P < 0.05), with GNU100 having a 17.6:1 consumption ratio compared with control. In the long-term study, all cats remained healthy, without any signs of gastrointestinal intolerance or illness. All diets were well accepted, resulting in similar ( P > 0.05) food intake, fecal characteristics, immunoglobulin A, and calprotectin, and dry matter, organic matter, fat, and crude protein digestibilities. Fecal butyrate was greater ( P = 0.02) in cats fed HD than cats fed LD or MD. Fecal indole was lower ( P = 0.02) in cats fed HD than cats fed LD. Cats fed CT had a higher ( P = 0.003) relative abundance of Actinobacteria than cats fed LD. The relative abundance of Peptococcus was impacted by diet and time. At 4 wk, Campylobacter was lower in fecal samples of cats fed HD. Overall, the data suggest that dietary GNU100 supplementation was highly palatable, well tolerated, did not cause detrimental effects on fecal quality or nutrient digestibility, increased fecal butyrate concentrations, and reduced fecal indole concentrations, supporting the safety of GNU100 for inclusion in feline diets and suggesting potential benefits on gastrointestinal health of cats.